Guide to Targeted Therapies: EGFR mutations in NSCLC - Cappuzzo, Federico; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2014)
Guide to Targeted Therapies: EGFR Mutations in NSCLC is a speedy and up-to-date review, which discusses EGFR mutations, testing methods and technology, current and emerging therapies, and resources that clinicians can provide to their patients. Busy healthcare professionals who want a quick review of EGFR gene mutations as well as a summary of current therapies will benefit from this succinct guide.
Introduction -- The Human Epidermal growth factor Receptor (HER) family: structure and function -- Methods for EGFR mutation testing -- Predictive and prognostic implications of EGFR mutations -- EGFR-targeted therapies in non‑small cell lung cancer -- Conclusions.
Keywords: Medicine; Oncology .; Pharmacotherapy; Respiratory organs—Diseases.; Medicine/Public Health, general; Oncology; Pharmacotherapy; Pneumology/Respiratory System